THE IMPLEMENTATION OF MOBILE LEGEND GAME TO INCREASE VOCABULARY AND LEARNING ACTIVENESS OF FIFTH GRADE STUDENT’S AT INSAN MANDIRI CENDEKIA PALEMBANG - Hasan Sadiqin; Indawan Syahri; Tahrun Tahrun (Esteem Journal of English Education Study Programme, 2022)
The objective of this study was to increasing vocabulary and learning activeness of fifth grade students at InsanMandiriCendekia Palembang. The method which used in this study is classroom action research where it took place in 2 cycles. The result of this study found that there was improvement of students’ vocabulary and learning activeness. The score of minimum completeness criteria of English lesson was 70. In vocabulary test cycle 1, there were 16students who passed the minimum completeness criteria or 49% of students. And in vocabulary test cycle 2, there were 29 students who passed the minimum completeness criteria or 89% of students. There was improvement of student’s vocabulary as 40%where from cycle 1 to cycle 2. The students’ learning activeness increased during the teaching learning process whereas it indicated the students’ learning activeness had increased.